2020
DOI: 10.1590/1414-431x20209849
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone antagonizes paraquat-induced cardiomyocyte senescence via the mIGF-1/SIRT1 signaling pathway

Abstract: Testosterone has been demonstrated to antagonize doxorubicin-induced cardiomyocyte senescence. However, whether testosterone prevents the paraquat-induced cardiomyocyte senescence is largely unknown. The detection of SA-b-gal activity was performed using senescence b-gal staining kit and the reactive oxygen species levels were determined by reactive oxygen species assay kit. The plasmids for insulin-like growth factor 1 shRNA (sh-mIGF-1), sirtuin-1 shRNA (sh-SIRT1), scramble shRNA (sh-NC), overexpressing mIGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Since we only had access to a limited sample pool for this study, we aimed at excluding individual variability by pooling the samples. Gender-specific analyses were carried out to avoid variations due to the influence of sex hormones, such as testosterone and oestradiol, in the modulation of SIRT1 expression [36][37][38]. While the male urine samples 24 h post-surgery revealed only seven cytokines as significantly altered, the female urine samples contained a plethora of significantly altered cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Since we only had access to a limited sample pool for this study, we aimed at excluding individual variability by pooling the samples. Gender-specific analyses were carried out to avoid variations due to the influence of sex hormones, such as testosterone and oestradiol, in the modulation of SIRT1 expression [36][37][38]. While the male urine samples 24 h post-surgery revealed only seven cytokines as significantly altered, the female urine samples contained a plethora of significantly altered cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…As adult mammalian cardiomyocytes are predominantly post-mitotic and cannot be expanded in vitro, we selected the proliferating HL-1 cardiac myocyte cell line to validate different therapeutical approaches [28]. These cells, even immortalized, maintain a cardiac-specific phenotype and have been previously used as experimental model for cardiomyocyte-induced senescence [29].…”
Section: Dox Induces Cell Cycle Arrest and Senescence In Hl-1 Cardiac...mentioning
confidence: 99%
“…To investigate whether the selective elimination of senescent cells would prevent long-term associated cardiac pathologies to DOX, we first established an in vitro model using the HL-1 cardiac myocyte cell line (Figure 18A). HL-1 cells represent a cardiac myocyte cell line that can be repeatedly passaged, and have been previously used to induce a cardiomyocyte senescence model (Yu et al, 2020), as even immortalized, these cells maintain a cardiac-specific phenotype and allow to obtain reproducible experiments (Claycomb et al, 1998). We first performed a doseresponse curve of DOX for 72 h and found that 100 nM treatment was enough to induce senescence in HL-1 cells without causing significant cell death, keeping cell viability up to 80% (Figure 18B).…”
Section: Induction Of Cellular Senescence In Hl-1 Cardiac Myocyte Cel...mentioning
confidence: 99%
“…An alternative for in vitro drug evaluation is the HL-1 cardiomyocyte cell line (Claycomb et al, 1998). These cells, even immortalized, maintain a cardiac-specific phenotype and have been previously used as an experimental model for cardiomyocyte-induced senescence (Yu et al, 2020). We treated HL-1 cells with low-dose DOX (100 nM) since it has been shown that cardiac cells undergo a senescence program rather than apoptotic damage under these conditions (Piegari et al, 2013;Spallarossa et al, 2009).…”
Section: Navitoclax-based Therapies Restore Cardiac Function In a Dox...mentioning
confidence: 99%